The Metacognitive Awareness Inventory (MAI). Defining informal trajectories, from metacognitive skills, to generate talent - Pignalberi, Claudio (Formazione & insegnamento, 2018)
The paper intends to present some research reflections and considerations about value that the subject attributes to its metacognitive capacity in formal, non-formal and informal contexts. Recent studies show that the best “learning trajectory” solves itself in the ability to reflect critically on the nature of the skills learned and on the attitude to think new styles and recognition methods of their own talent. Can metacognitive competence then justify this talented capability? Through which instruments? Can the informal context really re-discover itself as explorative land of new knowledge?